Produção volumétrica e predição de propriedades energéticas com uso de NIR para Eucalyptus benthamii - Benin, Cristiane Carla (2019)
Within the context of interest in the use of forest biomass and greater competitiveness and agility in forest processes, in a region that has limitations on the diversity of cold tolerant species and demands for wood consumption for energy, this work aimed to evaluate the volume and dry matter production of Eucalyptus benthamii at different ages and regions and use the Near Infrared Spectroscopy (NIR) and Partial Least Squares Regression (PLS) technique to determine wood and chip properties. The study was conducted in the region of Guarapuava-PR, considering three production regions of the species and three ages (5, 6 and 7 years), to investigate the production variables and properties associated with the energetic use of wood, seeking relationship in the data for the planning of forest production of the species. In addition of knowing the properties for decision making, data was also sought for the use of the forest as an energy input. For example the behavior of moisture loss of whole trees destined to the production of chip in different seasons of the year and models were constructed through PLS that allowed to determine variables of interest to a more quickly planning and consumption, employing the NIR technique. In general, it can be concluded that the dendrometric variables and the values of basic density were favored by the higher ages, however, it was also possible to verify evolution in the mean annual increment for the younger plantations, with positive reflexes in the increase in dry mass. No difference between ages and regions was observed for the energy properties of the wood. Interactions between ages and regions were observed and confirmed by hierarchical cluster analysis, which was able to efficiently stratify groups of regions and ages with higher and lower productivity, and with higher values of energy properties, as well as to provide information for planning and management of energy production. It was concluded positively on the energy production potential for E. benthamii in the study region and on the use of NIR models for prediction of basic density and moisture, capable of facilitating the determination of these properties by the rapidity in information, sampling form adopted and because it is a non-destructive technique.